1999
DOI: 10.1375/twin.2.2.115
|View full text |Cite
|
Sign up to set email alerts
|

A religious upbringing reduces the influence of genetic factors on disinhibition: Evidence for interaction between genotype and environment on personality

Abstract: I nfor mati on on per sonal i ty, on anxi ety and depr essi on and on sever al aspects of r el i gi on w as col l ected i n 1974 Dutch fami l i es consi sti ng of adol escent and young adul t tw i ns and thei r par ents. A nal yses of these data show ed that di ffer ences betw een i ndi vi dual s i n r el i gi ous upbr i ngi ng, i n religious affiliation and in participation in church activities are not influenced by genetic factors. The familial resembl ance for di ffer ent aspects of r el i gi on i s hi gh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…This could be similar to the effects of marriage providing social support as reported in a study that identified a diminished genetic influence on alcohol consumption in married female twins compared with their unmarried counterparts (Heath, Jardine, & Martin, 1989). Similar to studies on alcohol initiation, a religious upbringing has been shown to attenuate the heritability of behavioral disinhibition (Boomsma, de Geus, van Baal, & Koopmans, 1999). To our knowledge, no reports have investigated whether indices of religiosity influence the genetic liability for smoking initiation.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This could be similar to the effects of marriage providing social support as reported in a study that identified a diminished genetic influence on alcohol consumption in married female twins compared with their unmarried counterparts (Heath, Jardine, & Martin, 1989). Similar to studies on alcohol initiation, a religious upbringing has been shown to attenuate the heritability of behavioral disinhibition (Boomsma, de Geus, van Baal, & Koopmans, 1999). To our knowledge, no reports have investigated whether indices of religiosity influence the genetic liability for smoking initiation.…”
Section: Introductionsupporting
confidence: 80%
“…Although the studies by Koopmans, Slutske, van Baal et al (1999) and Boomsma et al (1999) found that a religious environment attenuates the heritable contributions to behavioral traits, they were limited by having to stratify their samples on the basis of twin pairs who were concordant for the presence or absence of a religious upbringing. To take full advantage of a continuum of a measure of religiosity, the present study used a method for modeling the genetic effects of a trait as a linear function of an environmental moderator (Purcell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In another Dutch twin study, interaction between personality and environment was observed [41]. Those twins with a religious upbringing did not demonstrate as many genetic effects on the development of so-called disinhibition, characterized by sensation seeking, enjoying drinks, wild parties, and numerous sexual experiences.…”
Section: Personality and Environmentmentioning
confidence: 93%
“…interactions (23,24). These are posited to explain the paradox of high heritability but strong environmental effects on IQ (see (25,26) for a discussion of thè Flynn effect' and multiplier effects).…”
Section: Measuring Heritabilitymentioning
confidence: 99%